Maria Czerepaniak-Walczak (2018). Proces emancypacji kultury szkoły. Warszawa: Wolters Kluwer, ss. 262 (Przegląd Pedagogiczny, 2019)
Recenzja publikacji: Maria Czerepaniak-Walczak (2018). Proces emancypacji kultury szkoły. Warszawa: Wolters Kluwer, ss. 262.